Residue Dynamics of Imidacloprid and Hexaconazole on Mango - Reddy, Narendra C; Kumari, Anitha D.; Lakshmi, B. K. M.; Reddy, Jagdishwar D (International Journal of Bio-resource and Stress Management, 2023)
The experiment on residue dynamics of imidacloprid and hexaconozole on Mango was conducted during April-May, 2010 on mango variety Banganpalli. Three sprays of imidacloprid 17.8 SL @ 125 ml ha-1 and 250 ml ha-1 while hexaconozole 5 SL @ 100 ml ha-1 and 200 ml ha-1 were given at panicle emergence, marble stage and maturity stage. Initial deposits of imidacloprid at single and double dose treated samples were 0.52 and 0.83 ppm, respectively which dissipated to Below Detectable Level (BDL) at 5 and 7 days after last spray respectively. The initial deposits of hexaconozole at single and double dose treated samples were 1.82 and 2.16 ppm respectively dissipated to BDL at 10 and 15 days after second spray. The waiting periods for imidacloprid on mango at single and double dose was 4.27 and 5.19 days respectively, after last spray while the waiting period for hexaconozole on mango at single and double dose was 7.62 and 10 days respectively after last spray.